Kirigami‐Inspired Reconfigurable Thermal Mimetic Device. Issue 12 (9th September 2022) - Wei, Hang; Gu, Jinxin; Ren, Feifei; Geng, Chenchen; Guan, Huan; Liang, Shuhui; Fan, Qingpu; Zhao, Jiupeng; Wang, Chengyu; Dou, Shuliang; Li, Yao
Abstract: Mimicry, a biological phenomenon whereby organisms can change their morphological characteristics to resemble another object, has stimulated the unprecedented development of devices that allow the manipulation of thermal emission. Herein, inspired by biological mimicry and the pattern evolution of Chinese Kirigami, this study demonstrates a universal and effective method to prepare devices that exhibit a reconfigurable and multilevel evolution of infrared (IR) thermal images based on vanadium dioxide (VO2 ). The significant discrepancy between the phase transition temperatures of VO2 with different tungsten doping fractions affords the reconfigurable response in thermal images to varying environmental temperatures. Particularly, the large degree of freedom afforded by evolution steps and local IR emissivity further consummates the thermal mimicry ability for diverse demands. Furthermore, the ultrafast response time, notable observation angle independence, and the active control system are also demonstrated. This study offers a new perspective for reconfigurable thermal mimetic devices and provides a new path for distinct applications such as IR communication, information encryption, and virtual/augmented reality. Abstract : Inspired by biological mimicry and the pattern evolution of Chinese Kirigami, devices which exhibit a reconfigurable and multilevel evolution of infrared (IR) thermal images based on VO2 are first demonstrated. A new perspective for reconfigurable thermal mimetic devices and a new path for distinct applications such as IR communication, information encryption, and virtual/augmented reality are proposed.